Tumor location as a risk factor for severe immune-related adverse events - Mike Wang; Michael Dougan; Daniel Leonard; Leyre Zubiri; Ryan J Sullivan; Kerry L Reynolds; Donald P Lawrence; Kamil Slowikowski; Alexandra-Chloe Villani; Steven M Blum; Ben Ouyang; Kelley A Grealish; et al. (Journal for ImmunoTherapy of Cancer)
Immune-related adverse events (irAEs) can cause severe morbidity and mortality, and they impair treatment with immune checkpoint inhibitors (ICI). Risk factors for irAEs are not well understood.We observed cases of patients having tumor deposits in their liver and lung during a workup of irAEs, which led us to hypothesize that the presence of tumor in an organ would increase the odds of developing severe irAEs in that organ. We then performed a retrospective cohort study that included patients who received an ICI for the treatment of cancer and were hospitalized between February 2011 and November 2021 at the Massachusetts General Hospital.We reviewed 384 patients hospitalized with concern for any irAE. A clinical diagnosis of ICI-related hepatitis occurred in 18% of patients with liver tumor deposits versus 8% of those without (OR 2.23, 95% CI (1.10 to 4.43), p=0.02). ICI-related pneumonitis occurred in 10% of patients with lung tumor deposits versus 4.4% of those without (OR 2.45, 95% CI (1.06 to 6.36), p=0.047). A combined analysis for liver and lung lesions demonstrated that the presence of tumor deposits in an organ increased the odds of having an irAE in that organ by over twofold (OR 2.31, 95% CI (1.34 to 3.99), p=0.002).Our results suggest that the presence of tumor deposits may represent a novel risk factor for severe irAEs in that organ.